Ruin Pubs in Budapest: Blessing or Curse? - Hajnal István (Real Estate Management and Valuation, 2018)
One of the most prominent tourist attractions in Budapest is the ruin pub district. Here, in ruined, rundown buildings, clubs that are mainly aimed at young foreigners, participants in party tourism, have sprung up like mushrooms. In Inner Erzsébetváros, the housing prices have significantly risen, since investors see the short- or long-term renting of the apartments as a good opportunity. Those who live in the district, however, find the noise of parties to be too loud, while the crowd and the dirt reduces their quality of life. The apartments located near these pubs are so-called “stigmatized properties”, since their value is shaped by the - positive or negative - opinion of the community. Using the method of hedonic analysis, this article examines the question of whether ruin pubs are a blessing or a curse to surrounding apartments, whether their effect increases or, on the contrary, decreases the apartments’ values.